1987
DOI: 10.1128/jb.169.12.5686-5691.1987
|View full text |Cite
|
Sign up to set email alerts
|

Effect of growth conditions on levels of components of the phosphoenolpyruvate:sugar phosphotransferase system in Streptococcus mutans and Streptococcus sobrinus grown in continuous culture

Abstract: The membrane-bound, sugar-specific enzyme II The phosphoenolpyruvate:sugar phosphotransferase system (PTS) concomitantly catalyzes the transport and phosphorylation of mono-and disaccharides in many bacteria (23,25). The overall reaction catalyzed by the PTS requires the membrane protein enzyme II (EII) and the general spluble proteins, enzyme I (El) and HPr, and in many instances a sugar-specific, soluble protein called enzyme III, or simply III (22,23,25). The oral streptococci transport a variety of sugar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
44
0

Year Published

1989
1989
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(49 citation statements)
references
References 30 publications
5
44
0
Order By: Relevance
“…Notwithstanding, neither this nor previous 2-DGE analyses (Len et al, 2003(Len et al, , 2004b have identified the integral cytoplasmic membrane glucose transporters EII man and EII glc , or the glucose permease of S. mutans required for uptake of glucose (Cvitkovitch et al, 1995;Vadeboncoeur et al, 1991) due to their hydrophobic structure. As a consequence, any change that the level of expression of these transporters may have on glucose uptake and subsequent metabolic rate cannot be surmised.…”
Section: D Displays Of Fractionated Proteinsmentioning
confidence: 99%
“…Notwithstanding, neither this nor previous 2-DGE analyses (Len et al, 2003(Len et al, , 2004b have identified the integral cytoplasmic membrane glucose transporters EII man and EII glc , or the glucose permease of S. mutans required for uptake of glucose (Cvitkovitch et al, 1995;Vadeboncoeur et al, 1991) due to their hydrophobic structure. As a consequence, any change that the level of expression of these transporters may have on glucose uptake and subsequent metabolic rate cannot be surmised.…”
Section: D Displays Of Fractionated Proteinsmentioning
confidence: 99%
“…The culture was maintained and assessed for purity as described previously (Hamilton & Ellwood, 1978). Cultures were grown in chemostats at a dilution rate ( D ) of 0.1 h-' in semi-defined medium (Hamilton & Buckley, 1991) under the following conditions: condition A (5 mM glucose at pH 7*0), which results in optimal glucose-PTS activity (PTS-0 cells), and condition B (50 mM glucose pH 5.5), which results in repression of the glucose-PTS (PTS-R cells) (Hamilton et a/., , 1989Vadeboncoeur et a/., 1987Vadeboncoeur et a/., , 1991.…”
Section: Methodsmentioning
confidence: 99%
“…As S. mutans growing in continuous culture is devoid of measurable glucose PEP-PTS activity at pH 5?0 (Vadeboncoeur et al, 1991), phosphoenolpyruvate is not required to initiate the phosphorylation cascade for this glucose uptake system. The levels of the final three enzymes in glycolysis at pH 5?0 were consistent with a reduced pool of phosphoenolpyruvate, since the reduced levels of enolase, in conjunction with an overall 2?8-fold increase in the four isoforms of pyruvate kinase, would be expected to convert 2-phosphoglycerate to pyruvate without any build-up of phosphoenolpyruvate.…”
Section: Glycolysismentioning
confidence: 99%
“…Two such systems exist in S. mutans: EII man , which has been well characterized, and EII glc , the existence of which is primarily based on physiological observations (Vadeboncoeur, 1984;Néron & Vadeboncoeur, 1987). However, continuous-culture studies suggest that S. mutans is completely devoid of EII man and EII glc activity at pH 5?0 (Vadeboncoeur et al, 1991). At this acid pH, the bacterium preferentially utilizes a non-PTS glucose permease system (Hamilton & St Martin, 1982;Dashper & Reynolds, 1990;Buckley & Hamilton, 1994), while maintaining a more alkaline cytoplasm by increasing the level of its proton-translocating F 1 F 0 -ATPase (Hamilton & Buckley, 1991;Cvitkovitch et al, 1995).…”
Section: Glucose Uptake and Proton Extrusionmentioning
confidence: 99%